Digital Transformation and Workforce Competency Improvement in Medan City: Opportunities and Challenges In the Industry 4.0 Era - Asdilvira, Beby (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2025)
The purpose of this study is to analyze the Influence of Digital Transformation on Competency Development, analyze the Influence of Digital Transformation on Increasing Workforce Competitiveness, analyze the Influence of Workforce Competency Development on Increasing Competitiveness, analyze the Role of Organizational Culture as a Moderating Variable. The population in this study were all workers in the formal and informal sectors in Medan City. The number of samples in this study was 200 respondents. The sampling technique used purposive sampling. This study uses a quantitative method with a Structural Equation Modeling (SEM) approach. The results of the study indicate that digital transformation has an effect on Workforce Competency Development, Digital Transformation has an effect on Increasing Workforce Competitiveness, Workforce Competency Development has an effect on Increasing Competitiveness, Strong organizational culture strengthens the influence of digital transformation and competency development on increasing competitiveness. The next implication is that the contribution of this new research lies in the integration of organizational culture as a moderating variable that strengthens the impact of digital transformation, thus filling the gap in previous research. In practice, strengthening a more innovative and adaptive organizational culture must be a priority so that digital transformation runs effectively and sustainably in Medan City